GEOCHEMICAL CHARACTERISATION OF LEAD IN SOILS, SEDIMENTS AND DUSTS OF IBADAN AND LAGOS, SOUTHWESTERN NIGERIA (2018)
The presence of Heavy Metals (HM) in soils, sediments and dusts are good indicators of contaminations of urban environment. Lead (Pb) is of grave concern amongst other HM because of its toxic impact on the environment and human health. Previous studies on HM have focused on the determination of concentrations and spatial distribution in various Nigerian cities. However, the geochemical fate and nature of Pb in Nigeria's environmental media is relatively unknown. This study was therefore designed to quantify and characterize Pb in soils, sediments and dusts from Ibadan and Lagos, Southwestern Nigeria. A total of seventy-three composite soils, 56 sediments, 17 road dusts and 10 representative rock samples were collected randomly from the cities of Ibadan and Lagos. Soil, sediment and dust samples were air-dried, screened, pulverised and sieved through 63µm nylon mesh. The sieved fractions and pulverised rock samples were digested using standard methods and analyzed for elemental components using Inductively Coupled Plasma-Mass Spectrometer, (ICP-MS). The chemical fractionations of Pb in the samples were determined by sequential analysis. Lead isotopes compositions of the samples were determined using quadrupole-based ICP-MS. Petrological and mineralogical analyses of rocks and other samples were determined using X-Ray Diffraction. The geochemical data were subjected to statistical analyses using Pearson correlation and R-mode factor analyses. Lead Isotopic Ratios (LIRs) and geo-accumulation indexes were used in evaluating and discriminating Pb sources. The concentration (ppm) of Pb in soils, sediments and dusts for Lagos were: 21.0-1963.0; 23.0-830.0 and 22.0-830.0; while in Ibadan soils and sediments were: 13.0 - 470.0 and 17.0-3288.0; respectively. For rock samples from Ibadan and Lagos, the values were: 2.9-20.3 and 2.8-7.2 ppm. Chemical fractionation (%) of Pb were: organic-sulphide (42.78-82.45); reducible (8.23-27.20); carbonate (9.00-43.60) and exchangeable (0.01-0.23) phases, respectively. Lead isotopes (ppm) showed that 204Pb ranged 1.72-47.41; 206Pb, 30.69-779.68; 207Pb, 27.00-664.46 and 208Pb, 65.67-1642.27 in Ibadan samples while that of Lagos were: 204Pb, 1.43 - 31.00; 206Pb, 25.26 - 509.74; 207Pb, 21.96-446.22 and 208Pb, 52.61-1089.93. Ibadan and Lagos rocks Pb isotopes (ppm) were: 204Pb, (0.02-0.07 and 0.03-0.06); 206Pb, (0.56-2.33 and 0.56-1.21); 207Pb, (0.38-1.56 and 0.47-1.01) and 208Pb, (1.19-4.13 and 1.22-2.57), respectively. Quartz, microcline, k-feldspar, plagioclase and kaolinite were the preponderant minerals in powdered rocks, soils and sediments. An enrichment of radiogenic Pb (206Pb, 207Pb and 208Pb) were observed in soils, sediments and dusts relative to their local background values, an indication of anthropogenic origin of Pb. The plots (208Pb/207Pb)/(206Pb/207Pb) revealed that over 80% of Pb in the environmental media was derived from anthropogenic sources. The LIRs of soils, sediments and dusts were characterised by lower 208Pb/206Pb ratios while the bedrocks had higher 208Pb/206Pb. Lead contents of the soils, dusts and sediments in most parts of the two cities were significantly higher than the natural background levels and held in chemically active geochemical phases. The lead types are more of the radiogenic types and this portend great risk to the environment and public health.